Pengaruh Sumber-Sumber Stres Kerja Terhadap Produktivitas Kerja Karyawan PT. Bank Aceh Syariah Cabang Banda Aceh - Ijal Fahmi (Jurnal EMT KITA, 2017)
This study was conducted to investigate and obtain empirical evidence, whether the sources of job stress, the dimensions of job design, characteristics of the individual, work group and organizational structure simultaneously have a significant influence on employee productivity PT. Bank Syariah Branch Aceh Banda Aceh as well as to determine whether the design work is a source of working sires that have a dominant influence on employee productivity PT. Bank Syariah Branch of Banda Aceh Aceh. Scope of this research is the stress of work with employee productivity. While this research is inferential research that intends to reveal a problem, situation or event by providing a thorough assessment, extensive and profound in terms of the relevant science. The population in this study are employees of PT. Bank Syariah Aceh Banda Aceh Branch totaled 43 and sampling was conducted by census so that the amount of the final sample to 43 people or involve the entire population in the study as the study sample. According to the research there are other factors beyond the research which may affect the employee's productivity PT. Bank Syariah Branch of Banda Aceh Aceh such as differences in education levels of employees, promotion and welfare.